1982
DOI: 10.1254/jjp.32.999
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous distribution of the cytochrome P-450 monooxygenase system in rat liver lobes.

Abstract: Abstract-Enzyme distribution in rat liver lobes was investigated using liver homogenate as the enzyme source. When the content or the activity was expressed on the basis of unit (gram) wet weight of liver tissue, the protein concentration was almost the same throughout the liver, but several enzymes were distributed heterogeneously within the liver. Cytochrome P-450 monooxygenase activity was higher in the median and right lobes of livers, while the left lobe contained a higher concentration of mitochondrial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The long-lasting effect of quinidine prolongs the biliary excretion rate of berberine, which may cause the saturation of the capacity-limited metabolism. Matsubara et al (1982) demonstrated that despite uniform protein concentration throughout rat liver, P450 monooxygenase activity was higher in homogenates prepared from the median and the right lobe relative to homogenate from the left lobe. Among these three lobes of the liver, the median lobe is the largest, with the thickest part in the center and positioned above the other two.…”
Section: Tsai and Tsaimentioning
confidence: 93%
“…The long-lasting effect of quinidine prolongs the biliary excretion rate of berberine, which may cause the saturation of the capacity-limited metabolism. Matsubara et al (1982) demonstrated that despite uniform protein concentration throughout rat liver, P450 monooxygenase activity was higher in homogenates prepared from the median and the right lobe relative to homogenate from the left lobe. Among these three lobes of the liver, the median lobe is the largest, with the thickest part in the center and positioned above the other two.…”
Section: Tsai and Tsaimentioning
confidence: 93%
“…UDP-glucuronyltransferase activity was determined in the presence of 0.03% Triton X-100 using 7-hydroxycoumarin as a substrate (13). Cytochrome P-450 in liver homogenate was detected spectropho tometrically as reported previously (14), and its content was calculated from the spectrum using the molar extinction difference of 104 mM-1 cm-1 for the absorption difference be tween the peak position (at about 450 nm) and 490 nm (15 …”
Section: Methodsmentioning
confidence: 99%
“…In a previous paper, we reported that CYP activities assessed by measurement of 7-alkoxycoumarin Odealkylase activities, which reflect various CYP isoforms 6 , showed apparent heterogeneity among the liver lobes of rats, that is, the activities in the median and right lobes were higher than those in the left lobe 7 . We also demonstrated that the susceptibility to CCl 4 -induced hepatotoxicities (CCl 4 hepatotoxicities) differed significantly among the various lobes of the rat liver, and that these differences were closely correlated with the heterogeneity of hepatic CYP activities in the different liver lobes 8 .…”
Section: Introductionmentioning
confidence: 93%
“…However, there were no other reports in the literature on investigation of the correlations between the susceptibility to CCl 4 hepatotoxicities and the hepatic CYP activities in the different liver lobes. Previously, we also reported alterations of hepatic enzyme distribution among the rat liver lobes following pretreatment with hepatic enzyme-inducing agents, phenobarbital (PB) or β-naphthoflavone (BNF) 7 . In the present study, we therefore compared the susceptibility to CCl 4 hepatotoxicities of the different liver lobes of rats enhanced by pretreatment with PB or BNF.…”
Section: Introductionmentioning
confidence: 99%